Education research in an intercultural context: An instance of interpretation, induction, and deduction - Giridharan, Beena (2016)
© 2017, IGI Global.This chapter presents a research framework for a study that focused on the development of a second language vocabulary acquisition model in a tertiary setting. The study was an investigation of lexical inferencing strategies specifically employed by second language (L2) learners, and of whether the explicit teaching of effective vocabulary strategies benefited learners in developing vocabulary. The framework presented here draws on theories of learning from the fields of education, applied linguistics, vocabulary development, and cognitive psychology. Several theoretical standpoints on vocabulary development, including factors such as lexical representation; theoretical constructs in reading comprehension; vocabulary processing in tertiary L2 learners; and socio-linguistics were considered in the design and inquiry process of the study, which was set in an intercultural context. The association of components of this research exercise to research paradigms is discussed.